PURPOSE EFFECT OF MOTIVATION AND WORK ENVIRONMENT PERFORMANCE OF DEPARTMENT OF INDUSTRY AND COMMERCE SOUTH SUMATERA PROVINCE - Linggariama Linggariama; Omar Hendro (KOLEGIAL, 2020)
Purpose Effect of Motivation and Work Environment Performance of Dinas Perindustrian dan Perdagangan South Sumatera Province. This type of research used in this research is associative research that is a research statement that is asking the relationship between two or more variables. Based on the results of the analysis that has been done, the results of this study can be concluded, first, Simultaneous Testing at a confidence level of 95% shows there is a significant influence between motivation and work environment on employee performance in the Department of Industry and Trade of South Sumatra Province. Second, partial testing at 95% confidence level shows that there is a significant influence of motivation on employee performance at the Industry and Trade Office of South Sumatra Province. Third, partial testing at the 95% confidence level shows that there is a significant influence of the work environment on the performance of employees in the Department of Industry and Trade of South Sumatra Province. Researchers provide recommendations to the Department of Industry and Trade of South Sumatra Province, namely first, leaders must increase their motivation through work environment conditions. Second, the leader gives adequate compensation. Third, the status and responsibilities so that employees are willing to improve performance voluntarily without coercion. Fourth, we must pay attention to the work environment of employees, especially through air temperature, noise and employee relations so that employees are willing to obey the rules and norms that apply in the company, so that employee performance also improves.